Boosting High-Rate Lithium Metal Batteries by Using Ether-Based Gel Polymer Electrolyte - Chenchen Zhang; Zuohang Li; Su Wang; Chen Li; Yuchang Si; Yue Ma; Dawei Song; Hongzhou Zhang; Xixi Shi; Lianqi Zhang (Energy Material Advances)
Ether-based electrolytes are widely used in lithium metal batteries owing to their higher compatibility with Li anodes compared to that of carbonate-based electrolytes. Compared to the concern with high voltage resistance characteristics, little attention has been paid to Li-ion transportation in ether-based systems. Hence, a 1,2-dimethoxyethane-based poly(methyl methacrylate-ethoxylated trimethylolpropane triacrylate) gel polymer electrolyte (named ME-GPE) was developed to realize rapid Li-ion transfer and construct compatible interfaces. The LiFePO4/ME-GPE/Li battery presents a high-rate (10 C) capacity retention of 85.6% after 200 cycles, while sluggish Li-ion transfer is exhibited in the liquid counterpart and a low capacity retention of 47.2% is presented after cycling. Density functional theory calculations show that the binding energies of Li+/DFOB− with a polymer matrix are much higher than those of the liquid electrolyte, which is conducive to the release and the rapid transfer of more Li ions. 7Li solid-state nuclear magnetic resonance exhibits a similar result; the higher frequency observed after cycling indicates a larger electron density variation and greater mobility of Li ions. Moreover, the interfacial characteristics were investigated, and Li-ion plating/stripping behaviors are regulated by abundant polar groups on polymers. Therefore, rapid Li-ion transfer capability and outstanding interface stability were simultaneously achieved for ether-based systems for the first time.